Endometriotic rectosigmoid stricture- a rare clinical entity - Kuppusamy, Balu; Misra, Shivanshu (Surgical Review: International Journal of Surgery, Trauma and Orthopedics, 2020)
Endometriosis is defined as the presence of endometrial mucosa implanted in locations other than the uterine cavity. Endometriosis is usually a disease involving women of reproductive age. A probable estimate is that 5–10% of women in their reproductive age have endometriosis. When they do occur, women experience mostly dysmenorrhea, heavy or irregular periods, pelvic pain or dyspareunia. The most common sites for endometriosis are the ovaries (60%), uterosacral ligament (60%), posterior cul-de-sac (28%), broad ligament (15%), bladder (15%) and sigmoid colon (7%). Colonic endometriosis is a rare sequelae. It usually presents vaguely with nonspecific abdominal pain, dyspareunia, tenesmus, rectal bleeding or painful defecation. Laparoscopy is considered the best diagnostic modality for endometriosis with a sensitivity of 97% and specificity of 77%. Although there are some rare cases of large bowel obstruction due to endometriosis in pre-menopausal women, it is extremely rare in the postmenopausal group. Our report highlights such a case, mimicking a malignant rectosigmoid stricture leading to a large bowel obstruction with minimal extracolonic endometriosis involvement. Conclusion: This case report shows that colonic endometriosis, although rare, can be significantly infiltrative and lead to complications such as a large bowel obstruction. Very rarely, isolated colonic involvement without pelvic endometriosis can mimic malignant obstruction as in this patient. Diagnosing this condition can be challenging and usually requires histological confirmation.